2008
DOI: 10.1016/j.astropartphys.2008.07.004
|View full text |Cite
|
Sign up to set email alerts
|

PoGOLite – A high sensitivity balloon-borne soft gamma-ray polarimeter

Abstract: We describe a new balloon-borne instrument (PoGOLite) capable of detecting 10% polarisation from 200 mCrab point-like sources between 25 keV and 80 keV in one 6 hour flight. Polarisation measurements in the soft gamma-ray band are expected to provide a powerful probe into high-energy emission mechanisms as well as the distribution of magnetic fields, radiation fields and interstellar matter. Synchrotron radiation, inverse Compton scattering and propagation through high magnetic fields are likely to produce hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 73 publications
0
35
0
Order By: Relevance
“…INTEGRAL was also used by Dean et al (2008) to detected gamma-ray polarized emission from the Crab. Recently Chauvin et al (2016) reported hard X-ray polarization measurements of the Crab pulsar with a balloon-borne polarimeter called PoGOLite (Kamae et al 2008). …”
Section: Polarization Of the Synchrotron Pulsed Emissionmentioning
confidence: 99%
“…INTEGRAL was also used by Dean et al (2008) to detected gamma-ray polarized emission from the Crab. Recently Chauvin et al (2016) reported hard X-ray polarization measurements of the Crab pulsar with a balloon-borne polarimeter called PoGOLite (Kamae et al 2008). …”
Section: Polarization Of the Synchrotron Pulsed Emissionmentioning
confidence: 99%
“…3. We have developed a CSA with fast slew rate and confirmed that we can select pure fast scintillator signal down to ∼15 keV, well below the threshold of photo-absorption site of Compton events [1].…”
Section: Pogolite Instrument and Signal Processingmentioning
confidence: 92%
“…T HE PoGOLite is a balloon-born instrument to measure the polarization of hard X-rays / soft gamma-rays in the 25-80 keV energy range [1], [2]. It is scheduled for launch in 2009 (engineering flight) and 2010 (science flight) and will observe polarization from astrophysical objects above 10 keV for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…We note that charged-particle background events will be eliminated with an efficiency of almost 100 % by the side (SAS) and bottom (PDC) BGO crystals. Instrument details can be found in [11]. See also [12] for signal processing details.…”
Section: Pogolite Instrumentation and Performancementioning
confidence: 99%